(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ground Air Tube Heat Exchanger are simple system have valuable feature to diminish energy consumption in uptown building which are operational with an active ventilation system. Through the conditioning system the air is equally passed through the tubes which are concealed under the ground. In this method air is pre-cooled for the era of summer. Solar energy gathered in soil may be utilised Ground Air Heat Exchanger, which have single tube or multiple tubes buried in ground. When the ventilation air drawn through tube(s), the air is heated in winter and cooled in summer due to the temperature difference between air and ground. By taking advantage of this free energy, we can reduce the energy consumption required for space cooling. The investigation model of Ground Air Heat Exchanger is made in Uni-Graphics NX 10 and a Computational Fluid Dynamics (CFD) methodology using ANSYS FLUENT 15.0 is used here to investigate the effect of air flow velocity and different inlet air temperature on the implementation of Ground Air Heat Exchanger system for summer cooling and it is validated by the experimental investigation.